PEMBUATAN DAN PENDAMPINGAN APLIKASI DATABASE USAHATANI PADA KELOMPOK TANI MAKMUR JAYA - Puryantoro; Moh. Furqan (Pusat Riset dan Inovasi Nasional, 2022)
Situbondo Regency is one of the largest mango-producing areas in East Java. In fact, this fruit has become a regional superior commodity. The target partner of the service activity is the Makmur Jaya Farmer Group in Sopet Village, Jangkar District, Situbondo Regency. This farmer group consists of 25 farmers by doing mango farming on an area of ​​40 ha. Partner problems, namely the activity of recording data on farmer group members and their production results are still manual, making it difficult to use group reports. The purpose of this service is to provide alternative solutions in the form of a farming database application and assistance in using the application. Prosperous Jaya Farmers Group. The implementation of the service program involves lecturers who have multidisciplinary expertise, namely agribusiness and programmers. The results of the service include the creation of a business database application and assistance to partners. Assistance starts from group data entry until the data is ready to print out. This service program can increase the knowledge of farmer groups in recording member data and the production results of each member of the farmer group. The farming database application has been given to the group leader as the person in charge of group administration.